Kualitas Fisik Lingkungan Kawasan Permukiman di Sempadan Rel Kecamatan Labuhan Ratu, Bandar Lampung - Panti Wahyuningsih; Rahayu Sulistyorini; Bambang Utoyo Sutiyoso (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Physical Environmental Quality of Residential Areas on the Railway Boundary Labuhan Ratu Sub-district, Bandar Lampung The high demand for land and limited availability have caused built-up land to move to suburban areas of the city. The concentration of activities, such as establishing settlements and higher education centers, has also influenced the development of built-up land around them. Low-income people take advantage of the opportunities available by utilizing vacant land as a place to live. Land use that is carried out continuously and uncontrollably has an impact on the railway boundary. This study aims to identify the physical condition of the environment in residential areas in Labuhan Ratu Subdistrict, especially in the railroad border area. The method used is descriptive qualitative. The results found that the existence of settlements on the railroad border in Labuhan Ratu Subdistrict is included in the category of illegal settlements. Infrastructure conditions such as drainage, lighting, waste management, clean water, and others could be better; the topographic conditions of the area also support this. Increasingly dense illegal settlements and poor infrastructure conditions will affect environmental conditions, such as decreased land balance and environmental quality.